O papel do professor de língua portuguesa como mediador para a construção de autoria nas produções de texto de alunos do ensino fundamental ll - Lima, Cássia Aparecida Toledo Rodrigues (2015)
The research presented focused on the application and analysis of a didactic proposal involving the theme: Construction of authorship in students´ text productions of elementary school students II, having a Portuguese teacher as mediator. From studies and empirical knowledge on the subject, some questions have emerged that stood out as the guiding research: The student knows and uses the discursive genre letter to interact and position himself as subject-author participatory socially? What strategies the teacher can develop for their students to put themselves in their textual productions, as authors? How the students, in their text, are constructed as authors? In order to find answers to this issue, the work brings as it main objective to promote activities of reading, viewing and discussion of a particular theme, using various genres of journalistic sphere, so that students have the foundation to their text production of discursive genre reader's letter. This genre was chosen in order to encourage elementary school students II to establish as active subjects in discursive communication and as a result to identify authorship traces in his writings, having the Portuguese teacher as the mediator. The theoretical basis for research, is based on Applied Linguistics (Moita Lopes, 2008); the principles of qualitative research (Bortoni-Ricardo, 2008); the discursive gender concepts and language from the perspective of Bakhtin (2010); studies on the verification of authorship indications (Possenti, 2002) (Bakhtin, 1997, 2003, 2010) and (krokocsz, 2012); dialectic of checking the historical-critical pedagogy (Gasparin, 2005). The participants of the research are students of the 6th grade and a Portuguese Language teacher/researcher. The generation of data of this project has as corpus twenty textual productions, being ten initial productions as a parameter for analysis authored by evidence and final ten productions in order to determine if there is evidence of authorship after intervention of a Portuguese teacher. After analyzing, it is concluded that elementary school students II succeeded through the mediation of a Portuguese language teacher to put themselves as subjects of their sayings